Effects of chlorhexidine and sodium hypochlorite on the microhardness of root canal dentin - Oliveira, Luciane Dias; Talge Carvalho, Claudio Antonio; Nunes, Willian; Valera, Marcia Carneiro; Ribeiro Camargo, Carlos Henrique; Cardoso Jorge, Antonio Olavo (Elsevier B.V., 2007)
Objective. The purpose of this study was to evaluate the effects of endodontic irrigants on the microhardness of root canal dentin.Study design. Thirty extracted single-rooted human teeth were used. The crowns were sectioned at the cementoenamel junction. Each root was transversely sectioned into cervical, middle, and apical segments, resulting in 90 specimens. The 3 sections of each root were separately mounted in an individual silicon device with acrylic resin. The specimens were randomly divided into the following 3 groups (n = 30), according to the irrigant solution used: (1) group 1, control (saline solution); (2) group 2, 2% chlorhexidine gluconate solution; and (3) group 3, 1% sodium hypochlorite (NaOCl). After 15 minutes of irrigation, dentin microhardness was measured on each section at 500 mu m and 1000 mu m from the pulp-dentin interface with a Vickers diamond microhardness tester in Vickers hardness number (VHN).Results. Data obtained were analyzed using analysis of variance and the Tukey test (5%). Specimens irrigated with 2% chlorhexidine (group 2) or 1% NaOCl (group 3) presented lower values of dentin microhardness, with significant difference in relation to the control group (P < .05).Conclusion. It could be concluded that chlorhexidine and NaOCl solutions significantly reduced the microhardness of root canal dentin at 500 mu m and 1000 mu m from the pulp-dentin interface.